2009
DOI: 10.3177/jnsv.55.412
|View full text |Cite
|
Sign up to set email alerts
|

Dietary <i>Trans</i> Fatty Acids Suppress the Development of Spontaneous Atopic-Like Dermatitis in NC/Nga Mice

Abstract: SummaryAlthough several studies have shown that the type and degree of unsaturation of fatty acids alter the production of proinflammatory mediators, there have been few studies in which the effects of trans isomers on allergic responses were evaluated. NC/Nga (NC) mice raised in conventional conditions develop spontaneous atopic dermatitis-like lesions with IgE hyperproduction. We used this model to evaluate the effect of dietary trans fatty acids (TFAs) on the development of spontaneous dermatitis. NC mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…While the influence of TFA derivatives incorporated in the skin is poorly understood, LC n-3 PUFA are precursors of eicosanoids and docosanoids [72], and already described as having antiapoptotic properties [31]. While MUFA present in FO, SO and HVF groups did not alter the skin's sensitivity to sunburn or its time to redden [73], few studies on the influence of TFA on skin health have been carried out so far [40,55]. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the influence of TFA derivatives incorporated in the skin is poorly understood, LC n-3 PUFA are precursors of eicosanoids and docosanoids [72], and already described as having antiapoptotic properties [31]. While MUFA present in FO, SO and HVF groups did not alter the skin's sensitivity to sunburn or its time to redden [73], few studies on the influence of TFA on skin health have been carried out so far [40,55]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[39] for 90 days and thereafter, one half of the mice in all experimental groups were exposed to UVR, totaling eight experimental groups (n = 7). The length of time chosen for supplementation (90 days) was based on previous studies by other laboratories evaluating the influence of TFA [40] and an oil mixture containing vitamin E [41] on the skin of mice. The body weight gain of the animals, as well as the daily food consumption was monitored throughout the experimental protocol.…”
Section: Methodsmentioning
confidence: 99%
“…We speculate that the TFA intake-mediated increase in IL-17A expression during inflammation may disrupt normal intestinal immunity, thereby inducing hypersensitivity and further exacerbating inflammation. Sakai et al demonstrated that the levels of IFN-γ, which is produced primarily by Th1 cells, are notably higher in mice fed TFAs than in control mice [46], suggesting a role for Th1 cells in TFA-induced aggravation of DSS colitis. However, in our study, the mRNA levels of IFN-γ, which is produced primarily by Th1 cells, and the mRNA levels of T-bet, a key Th1-inducing factor, in both the colonic mucosa and the MLNs, did not differ between DSS-treated mice fed the TFA diet and mice fed the TFA-free diet, suggesting few roles for Th1 cells in the aggravation of DSS colitis.…”
Section: Discussionmentioning
confidence: 99%
“…A single supplement dosage from prenatal period until adulthood of the first generation was used to study its influence on skin incorporation in this life period as related to UVR‐induced cutaneous alterations, in accordance with previous research protocols regarding generations . The duration of post‐weaning supplementation (90 days) was chosen based on previous studies that assessed the influence of FA on the skin health of rodents .…”
Section: Methodsmentioning
confidence: 99%